COMPETENCY MAPPING - A MANAGERIAL PERCEPTION (A STUDY OF HDFC BANK LTD.) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Competencies are components of a job which are reflected in behaviour that is observable in a workplace. The common elements most frequently mentioned are knowledge, skills, abilities, aptitudes, personal suitability behaviour and impact on performance at work. The main emphasis of organizations today is on competence. Gone are the days when people used to talk in terms of skill sets, which would make their organizations competitive. There has been a shift in focus, and organizations have begun to believe in excelling and not in competing. The Competency mapping affects the existing competencies of managers. Therefore, the papers attempts to measure the role of competency mapping in the efficient performance of the employees at manager levels and determine various functional areas, where the competency mapping can be proved beneficial. The research of study is based on the primary data collected by the mean of questionnaire form the employees of five branches of HDFC Bank, located at different places in Amritsar. Similarly, the result of study prove that, the competency mapping is necessary for the performance and future growth of bank, because the growth and development of every business is based on the efficient and satisfied working staff.